MRC avanzata e genere: una visione pluriprospettica /multidimensionale - Anna Laura Fantuzzi; Elisa Berri; Lida Tartagliolne; Marcora Mandreoli; Rossella Giannini; Sara Dominjanni; Silvia Porreca (AboutScience Srl, 2024)
Chronic kidney disease (CKD or CKD [Chronic Kidney Disease]) is present in approximately 7% of the world population: several studies have highlighted socio-cultural discrimination, to the detriment of women, in referral to specialist nephrological care and access to dialysis and transplantation. Globally, gender discrimination limits the possibility of access to education, medical care and involvement in clinical trials. Women on dialysis have different comorbidities than men; the choice to follow a predialysis process and the subsequent orientation towards dialysis treatment are certainly influenced by gender as is the choice of dialysis access. As regards kidney transplantation, women are more likely to offer themselves as donors rather than to be beneficiaries. Conventional knowledge supports the belief that there are gender differences in the acquisition, preparation and consumption of food, for this reason it is essential to consider the variables that come into play when defining and agreeing treatment paths, in particular in taking care of people with chronic diseases such as CKD